Comparison study between NPWM and NSVPWM strategy in FSMC control of stator reactive and active powers control of a DFIG-based wind turbine system - Habib Benbouhenni; Zinelaabidine Boudjema; Abdelkader Belaidi (Institute of Advanced Engineering and Science, 2020)
In this work, we present a comparative study between neural space vector pulse width modulation (NSVPWM) and neural pulse width modulation (NPWM) technique in fuzzy-sliding mode control (FSMC) of stator active and stator reactive power control of a doubly fed induction generator (DFIG) for wind energy conversion systems (WECSs). Two strategies approach using FSMC-NSVPWM and FSMC-NPWM are proposed and compared. The validity of the proposed strategies is verified by simulation tests of a DFIG (1.5MW). The reactive power, electromagnetic torque, rotor current and stator active power is determined and compared in the above strategies. The obtained results showed that the proposed FSMC with NSVPWM strategy has stator reactive and active power with low powers ripples and low rotor current harmonic distortion than NPWM strategy.